Ultra-high quality factor and low dielectric constant of (Zn0.5Ti0.5)3+ co-substituted MgAl2O4 ceramic. Issue 16 (15th August 2021) - Yang, Fan; Lai, Yuanming; Zeng, Yiming; Zhang, Qin; Han, Jiao; Zhong, Xiaoling; Su, Hua
Abstract: In this study, MgAl2 O4 -based ceramics with high quality factor (Qf) and low dielectric constant (εr ≤ 10) were obtained by fabricating MgAl2- x (Zn0.5 Ti0.5 ) x O4 ( x = 0–0.5) ceramics via conventional solid-state reaction method. Excellent microwave dielectric properties were achieved for samples at x = 0.5 and sintered at 1550 °C, i.e., εr = 9.86, Qf = 263 900 GHz (five times better than that for x = 0 sample) and τf = −92 ppm/°C. The X-ray diffraction (XRD) patterns displayed characteristic peaks of MgAl2 O4 with spinel structure. MgTi2 O5 and MgTiO3 were considered as secondary phases. Scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS) and relative density analysis indicated that ultra-high Qf values were dominated by dense microstructure, secondary phase and cation vacancies; whereas εr values were mainly affected by secondary phase and ionic polarizability. MgAl2- x (Zn0.5 Ti0.5 ) x O4 ceramics with excellent microwave dielectric properties have potential application in millimeter-wave communication, dielectric filters, dielectric antennas and resonators.